2016
DOI: 10.3390/su8080731
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Green ICT Adoption in Organizations: A Theoretical Perspective

Abstract: Information and communication technologies (ICT) are present in almost all fields of human activity. The expansion of their use should be balanced by the results of the studies on the negative effects on the environment. The relationship between these technologies and the environment is relatively new. The application of environmental criteria is commonly referred to as green ICT or green computing. Awareness of the importance of the ecosystem has led to increased interest in its protection both in production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…In any case, in the context of the reality on ground, green computing awareness has to be intensified across all strata of businesses to ensure the environment is not devastated [3] by ICT-related activities. For instance, corporate organizations through their corporate social responsibility (CSR) portfolio [24] could raise green computing awareness among computer users and merchants [25]. Such campaigns will purely target Sustainability 2017, 9, 1857 4 of 17 acceptable environmental behaviours [17] that protect and preserve the natural and social environments for sustainable development.…”
Section: Green Computing and Sustainable Developmentmentioning
confidence: 99%
“…In any case, in the context of the reality on ground, green computing awareness has to be intensified across all strata of businesses to ensure the environment is not devastated [3] by ICT-related activities. For instance, corporate organizations through their corporate social responsibility (CSR) portfolio [24] could raise green computing awareness among computer users and merchants [25]. Such campaigns will purely target Sustainability 2017, 9, 1857 4 of 17 acceptable environmental behaviours [17] that protect and preserve the natural and social environments for sustainable development.…”
Section: Green Computing and Sustainable Developmentmentioning
confidence: 99%
“…Awareness of ecosystem services and their associated resources and services has increased in ICT production and consumption [28]. The installment, computation, maintenance, and energy requirements of these systems can have negative environmental impacts.…”
Section: Discussionmentioning
confidence: 99%
“…The installment, computation, maintenance, and energy requirements of these systems can have negative environmental impacts. Recently, numerous studies have indicated that balancing ICT usage with the potential negative environmental effects is essential for the development of ICTs [28][29][30]. This relatively new area of research, known as green ICT or green computing, attempts to develop environmental guidelines suitable for curbing the negative effects of ICTs [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to adopt green ICT depends on the expected benefits and investments. This decision depends on costs, competitiveness, financial support, managers and employees' characteristics and skills, legal regulations, supply, and demand [13]. In the last few decades, many projects have applied ICT systems to numerous fields, including the environmental monitoring at organizations.…”
Section: Literature Reviewmentioning
confidence: 99%